Optimalisasi Portofolio Saham dengan Simulasi Monte Carlo untuk Pengukuran Value at Risk (VaR) - Sarah Hardiana; Muhammad Subhan; Dewi Murni (Journal of Mathematics UNP, 2021)
Abstract – Value at Risk (VaR) is the one of statistical measurement tools that measures the maximum expected loss from an investment on the certain confidence level and certain time period on normal market condition. One of the method to determine VaR value is Monte Carlo Simulation Method. The purpose of this paper is forming the optimal portfolio with VaR value. The type of reseaech is applied research using secondary data that is daily closing price stock LQ-45 about 6 months. The steps are determine the parameters, simulating the return value randomly, and calculate VaR value average. Based the result generated the optimal portfolio at the rate of return specified and by the smallest VaR value.Keywords – Portfolio, Value at Risk (VaR), Monte Carlo Simulation, stock